THE IMPACT OF SOCIAL MEDIA ON FOMO (FEAR OF MISSING OUT) AMONG HIGHER EDUCATION STUDENTS - Nurul Mawaddah; Fatimah Hidayahni Amin; Abdul Wahid; Nurharsya Khaer Hanafie (International Journal of Business English and Communication, 2025)
This research aims to determine the impact and influence of social media on FoMO among higher education students. The study utilizes a qualitative research design with a descriptive approach. Data collection techniques include distributing questionnaires and conducting in-depth interview. The findings of this study highlight a significant relationship between the level of social media engagement and increased FoMO, as well as identifying specific behaviors that affect students' FoMO levels. Additionally, the study identifies specific social media behaviors, such as constantly checking for updates, comparing oneself to others, and fearing exclusion from social events as contributing factors to heightened FoMO. The research underscores the need for awareness and critical engagement with social media to mitigate its negative effects on college students.